“Colonial Question” in European Collective Memory: Review of Recent Studies - Galina Nelaeva (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. The “critical turn” in modern humanities and social sciences has led researchers to rethink the contemporary global processes in terms of the inclusion/exclusion of actors in accepted narratives. The “women’s question” and “the voice of the subalterns” represent only a small part of hotly debated topics in academia and in the public sphere. Research on the memory of the traumatic past in European countries is also highly topical due to the fact that when faced with modern challenges, the European Union is trying to “re-assemble” its identity and declare itself as a global player, an actor with unity and certain “common values,” among which is shared memory of the past. Methods and materials. Through comprehensive analysis of recent research on the memory of colonialism in European countries, four countries are compared: France, Great Britain, Belgium, and the Netherlands. Analysis. A group of factors is identified that influence the perception of the past and its representation in urban places, in public discussions, on television, in mass culture, etc. Such factors include, in particular, the presence of a large and organized diaspora from the former colonies, the spread of modern technologies, the activities of veterans’ and former settlers’ associations, the interest of the younger generation in their past, etc. Results. As the study shows, the memory of the past continues to be a complex and contradictory phenomenon in the cultural and political life of European countries. Official discourses of memory are constantly challenged by actors who disagree with the interpretation of past events. The process of accepting the tragic past is not always accompanied by concrete measures, such as the payment of reparations, ceremonies to commemorate the victims of atrocities, memorial days, etc., and among the population there is still nostalgia for the colonial past.